Music for pain in healthy neonates - Nessie Amelia Ramli; Afifa Ramadanti; Indrayady Indrayady; Yuli Doris Memy (Paediatrica Indonesiana, 2021)
Background The neonatal pain threshold is 30-50% lower than in adults and older children because of immature pain inhibition function in nervous centers. Acute pain in neonates results in behavioral, physiological, and cerebral blood flow changes that may lead to intraventricular bleeding and periventricular leukomalacia. Music is believed to reduce pain perception as it distracts, influencing the parasympathetic and sympathetic nervous system by decreasing pulse rate, blood pressure, and breathing, hence, promoting a relaxed state. Objective To evaluate effects of music intervention on physiological parameters and pain perception in healthy newborns undergoing a painful medical procedure (immunization injection). Methods This was a double-blind, randomized control trial study. A recorded instrumental lullaby â€œNina Boboâ€ was given for 5 minutes to the music group and no music for control, prior injection of Hepatitis B 0. The evaluation of heart rate and SpO2 were performed at baseline, 30 seconds, and 5 minutes after injection. Pain perception were measured by Neonatal Infant Pain Scale (NIPS) at 30 seconds and 5 minutes after injection. Results Total of 51 subjects were enrolled. There were no difference of SpO2 and NIPS between both music and control groups. Music improved heart rate after 30 seconds and 5 minutes after injection, median 126 (range 55-149) bpm from median 136 (range 78-154) bpm, and even lower than baseline [mean 128.9 (SD 12.5) bpm; P=0.019]. The control showed no improvement of heart rate mean 124,34 (SD 18,45) from 124,73 (SD 18,39); P=0.875There were no significant differences between the 2 groups. Conclusion Music is not effective in improving oxygen saturation, heart rate, and is not effective in reducing the degree of pain.